Organización C ontable a la E mpresa “Comercial Joyeria y Relojeria Danny” del cantón el Pangui, provincia de Zamora Chinchip e, periodo del 01 de abril al 30 de junio de 2022 - Sarango Minga, Doris Birmania (2023)
The present thesis called ACCOUNTING ORGANIZATION OF JEWELRY AND WATCHES DANNY FACTORY FROM EL PANGUI COUNTY PROVINCE OF ZAMORA CHINCHIPE, DURING APRIL 01ST TO JUNE 30TH OF 2022, it was developed with the main goal to improve the financial activities, and for that it was as a bibliographic reference related with the appropriate theory through the analysis of concepts and definitions of commercial accounting, that allows to carry out the practical part through the collection, registry and interpretation of the transactions of product’s turn with the truthful and faithful information that allows the owner to take the best decision. To accomplish the stablish objectives it was necessary the use different types of research investigation, for the practical part it was necessary the multiple account stocktaking or daily inventory that enable take a detail control all over different account and get the usefulness of gross profit; the plan and the manual of the accounts were done according to the necessities and activities of the factory, the inventory gathering across of values verification, real state and obligations; a detail shopping assistant was created, sells, accounts receivable, counts to pain and pay role all of them make easy the economic operations register; the accounting process was done taking into account the initial situation, also the economic facts register in the daily book, the main book, the checking balance, work sheet with it regulations and adjusted, the state’s results, financial situation, cash flow statement and its explicative notes. Once the entitled worked has finished it is considered very important the account organization of the factory, in as much as make activities will be easier to be done and more efficient way according to their needs. The financial accurate was obtained, across reliable and timely information reflected in the financial states, where it was determined and net profit to the owner, so based on this take appropriate decisions to the economic growing of his commercial.